The Influence of Learning Attitudes and Motivation on Students' Learning Achievement - Yusup, Muhammad; Marzani, Marzani; Lubis, Toib; Anggraeni, Gina Silpa (Graduate Program Magister Manajemen Pendidikan, 2023)
The goal of this study was to see how learning attitudes and motivation affected student learning success at MAN 1 Batanghari. This is a quantitative study using a survey approach. This study's population included students from classes X and XI, with a sample size of 52 students. All respondents completed three types of instruments based on learning attitudes, motivation, and success in the learning process. The findings indicate that 1) learning attitudes have a significant impact on learning success. The better the learning attitude of students, the more successful the student learning process at MAN 1 Batang Hari will be;Â 2) Motivation has a significant impact on student learning success. The better the students' motivation, the better their success in the student learning process at MAN 1 Batang Hari; and 3) learning attitudes and motivation both have a significant effect on student learning process success. Whereas the better the learning attitude and motivation, the better the student learning process success.